(untitled) (Research in Agriculture Livestock and Fisheries, 2019)
The study was conducted to determine the present status of fisheries and socio-economic conditions of the fisher’s community of Eshulia beel at Gouripur upazila under Mymensingh district for a period from February to November, 2013. Relevant information and pertinent data were collected by personal observation and other three participatory methods such as questionnaire interview, focus group discussion (FGD) and cross-check interview. A total of 58 fish species belong to 18 families were identified in the catches of different gears. Among them 37 species were resident, 14 species were non-resident and 7 species were exotic. Thirteen different kinds of fishing gears were identified under 5 major groups including 5 nets, 3 traps, 2 hooks, 2 spears and khata/zag in the beel. It was found that 65% of the fishermen were Muslim and 35% were Hindu. Most of the fishermen belonged to the age group of 36-50 years. In case of education, 32.5% were illiterate, 40% can sign only, 15% of the fishers had literacy up to primary level , 7.5% had literacy up to secondary level and 5% had higher secondary and above. 75% of the fishermen’s houses are katcha, 17.5% are tinshed and only 7.5% are half building. About 5% of the fishermen had high (TK 100000-TK 200000) income; 42.5% had medium (TK 51000-TK 100000) income and 52.5% had low (TK 25000-TK50000) income. No fisheries management regulations were followed in the beel. Recommendations were made to improve beel fisheries management through fish stocking, habitat restoration and active community participation for sustainable catch. Res. Agric., Livest. Fish.6(2): 353-361, August 2019